Pengaruh Pasir Laut Sebagai Alternatif Pengganti Pasir Sungai Pada Campuran Beton Mutu Normal: The Effect Of Sea Sand As An Alternative Substitute For River Sand In Normal Quality Concrete Mixes - Lilis Indriani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The demand for concrete as a construction material continues to increase along with infrastructure development, resulting in intensive use of river sand as fine aggregate and potential environmental degradation. Therefore, sustainable alternative materials are required, one of which is sea sand that is abundantly available in coastal areas. This study evaluates the feasibility of sea sand from Kuala Pembuang, Seruyan Regency, as a substitute for river sand in normal-strength concrete and analyzes the relationship between sea sand content and concrete compressive strength. The research employed a laboratory experimental method with sea sand substitution levels of 0%, 50%, and 100%. Compressive strength tests were conducted at curing ages of 7 and 28 days, and the data were analyzed using quadratic polynomial regression. The results show that the relationship between sea sand substitution and concrete compressive strength can be expressed by the equation Y=317.5+0.7550X+0.0175X2, indicating that variations in sea sand proportion significantly influence concrete strength. Based on these findings, sea sand from Kuala Pembuang has potential to be used as an alternative fine aggregate for normal-strength concrete at appropriate substitution levels.